#TITLE_ALTERNATIVE# - TRI HANURANTO (NIM 23295039), AHMAD
Broadband Integrated Service Digital Network (B-ISDN) are high speed services infrastructure that expected to support diverse applications such as voice, data, and video. Different applications have different traffic characteristics and require different quality of service (QoS). ATM networks are relatively more complexes than conventional networks base on how ATM networks connect and superpose different traffic type. Traffic type that serviced is not only have continuous and fix rate, but often they have varies rate and bursty streams. This research addressed to study with simulation where heterogeneous traffic are multiplexed and how heterogeneity traffic streams (especially varying level of burstiness) affect cell loss ratio (CLR). Traffic streams used in this simulation are two types; constant bit rate (CBR) and variable bit rate (VBR). The use of cell priority mechanism is also investigated. We consider traffic arrival model is markov modulated poisson process (MMPP). Simulation yields show that buffer size in server or multiplexer and number of traffic source significant effect to cell loss ratio. These effects tend to linear for increase of VBR traffic source. The use of cell priority mechanism is effective to protect cell loss ratio of high priority traffic. These mechanisms generally not affect to average cell delay in the networks. More bursty VBR traffic is superposed increase cell loss ratio, both to VBR traffic self and CBR traffic.